Screening of depression in chronic kidney disease patients undergoing haemodialysis. - Muhammad Fahad; Kandhro, Abdul Hafeez; Khan, Sher Wali (International Journal of Endorsing Health Science Research, 2021)
Background: Depression is a common psychiatric disorder among chronic kidney disease (CKD) patients, and it has affected the morbidity & mortality rate of CKD patients. This study aims to determine the frequency and severity of depression in CKD patients on hemodialysis. Methodology: This cross-sectional study was conducted at the Department of Nephrology, Abbasi Shaheed Hospital, Karachi. A total of 251 patients of age between 18-60 years admitted with End-Stage Renal Disease ESRD and getting maintenance haemodialysis were included. Patients diagnosed with psychiatric, neurological illnesses and taking antidepressants were excluded from the study. Demographic and clinical characteristics of CKD patients were obtained on the structured questionnaire, and the Hospital Anxiety and Depression Scale (HADS) was utilized. Results: Of the total, 127 (50.6%) were males, and 124 (49.4%) were females, with a mean age of 53.94 ± 14.67 years. Approximately 65% of ESRD patients were suffering from depression. Among these, the patients who were receiving maintenance dialysis were suffering from a mild form of depression (33.1%) (HADS 5-9), 22.3% had moderate depression (HADS 10-14), and 9.6% had severe depression (HADS>15). Moreover, a significant difference has been observed between age and creatinine levels. Conclusion: Around 10% of the patients had severe depression, which enhances the attention towards it. Multicenter studies should be conducted across Pakistan to identify the extent of the problem.